Application of Single and Double Component Wood Bleaching Chemicals on Surface Properties of Naga (Brachystegia cynometroides) Wood - Hüseyin Peker; Göksel Ulay; Ümit Ayata (Masyarakat Peneliti Kayu Indonesia, 2024)
In this study, some surface changes (color parameters, whiteness index (WI*), and glossiness) occurring after the application of single [oxalic acid (C2H2O4)] and double component [sodium hydroxide (NaOH) + hydrogen peroxide (H2O2)] wood bleaching chemicals on naga (Brachystegia cynometroides) wood were investigated. The bleached surfaces were compared with the unbleached surfaces. According to the obtained results, the ∆E* values were determined as 2.99 for C2H2O4 chemical and 16.95 for NaOH + H2O2 chemical. Significant results were found for all tests in the analysis of variance. Increases in b* and C* values were observed with C2H2O4, while decreases were observed with NaOH + H2O2 chemical. With both wood bleaching chemicals, increases were found in WI* values in parallel directions to the fibers, as well as in ho and L* values, while decreases were obtained in glossiness values at 60 and 85 degrees in both parallel and perpendicular directions to the fibers, and in a* values.